1999
DOI: 10.1177/0093854899026004003
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Postrelease HIV Risk among Male Prison Inmates

Abstract: Male prison inmates within 2 weeks of release were recruited to evaluate a prerelease HIV prevention intervention. A total of 414 inmates were randomly assigned to receive the intervention or to a comparison group. All participants completed a face-to-face survey at baseline; high rates of preincarceration at-risk behavior were reported. Follow-up telephone surveys were completed with 43% of participants; results support the effectiveness of the prerelease intervention. Men who received the intervention were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 11 publications
1
64
0
Order By: Relevance
“…The significance of this relationship endured multiple adjustments for preceding confounders and additional post hoc analyses controlling for baseline levels of unprotected vaginal sex. These findings are consistent with previous research linking incarceration with unprotected sex 6,7,17,33 but build on them by defining a temporal ordering of exposure and outcomes. Furthermore, this is the first known study to highlight a temporal relationship between arrest and sexual risk.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The significance of this relationship endured multiple adjustments for preceding confounders and additional post hoc analyses controlling for baseline levels of unprotected vaginal sex. These findings are consistent with previous research linking incarceration with unprotected sex 6,7,17,33 but build on them by defining a temporal ordering of exposure and outcomes. Furthermore, this is the first known study to highlight a temporal relationship between arrest and sexual risk.…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3][4] HIV/STI prevalence in criminal justice populations is higher than in the general population for nearly every demographic grouping of men, and many studies document increased levels of sexual risk behaviors associated with criminal justice involvement. [5][6][7] A recent review summarized that incarcerated populations (compared to the general population) initiate sex at an earlier age, have more sexual partners, and use STI prevention methods more inconsistently. 1 Although there is a clear disparity in HIV/STI prevalence and risk among male offenders, a question which has not been adequately addressed is whether criminal justice involvement uniquely contributes to a confluence of HIV/STI risk factors for these men.…”
Section: Introductionmentioning
confidence: 99%
“…More methodologically robust research is needed to determine fully whether peer interventions in prison are effective, as concluded by a recent systematic review published in this journal (Wright et al, 2011). Empirical evidence does exist, however, that demonstrates positive impacts of peerbased programmes on certain health outcomes, including: prisoners' knowledge of HIV (Collica, 2002, Scott et al, 2004, Bryan et al, 2006, Ross et al, 2006 and uptake of HIV testing (Zack et al, 2013); knowledge of sexually transmitted infections (Sifunda et al, 2008); beliefs, intentions and reported increases in condom use (Magura et al, 1994, Grinstead et al, 1999, Bryan et al, 2006; and increased inclination to practice safer drug using behaviours (Collica, 2002). Moreover, some have argued that peer schemes have been instrumental in reducing suicide and self-harm in prisons (Snow andBiggar, 2006, Samaritans, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such interventions have incorporated individual risk reduction delivered through case management, peer education, and/or motivational interviewing models and many have seen success in prevention of HIV risk [48][49][50][51]. However, the persistently high levels of infection among inmates suggest alternative intervention strategies would strengthen risk reduction efforts during community re-entry.…”
Section: Discussionmentioning
confidence: 99%